2019
DOI: 10.3390/molecules24112046
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from Five Ericaceae Species Leaves and Their Related Bioavailability and Health Benefits

Abstract: Some species of the Ericaceae family have been intensively studied because of the beneficial health impact, known since ancient times, of their chemical components. Since most studies focus on the effects of fruit consumption, this review aims to highlight the phenolic components present in the leaves. For this purpose, five species from Ericaceae family (bilberry—Vaccinium myrtillus L., lingonberry—V. vitis-idaea L., bog bilberry—V. uliginosum L., blueberry—V. corymbosum L. and bearberry—Arctostapylos uva-urs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 95 publications
1
94
0
5
Order By: Relevance
“…Walnut leaves are considered to be a rich source of phytochemicals, such as phenolics, flavonoids, and flavonols with free-radical scavenging properties, and are an important exogenous antioxidant source with a role in oxidative stress balance [22]. All groups of phenolic compounds are present in the leaves of bilberry, including high levels of anthocyanins or procyanidins, which have proven anti-radical activity [10]. The walnuts and bilberries are considered significant contributors to carotenoid and tocopherol daily intake [23], but to our knowledge, very little is known about the concentrations of these compounds in leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walnut leaves are considered to be a rich source of phytochemicals, such as phenolics, flavonoids, and flavonols with free-radical scavenging properties, and are an important exogenous antioxidant source with a role in oxidative stress balance [22]. All groups of phenolic compounds are present in the leaves of bilberry, including high levels of anthocyanins or procyanidins, which have proven anti-radical activity [10]. The walnuts and bilberries are considered significant contributors to carotenoid and tocopherol daily intake [23], but to our knowledge, very little is known about the concentrations of these compounds in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Bilberry (Vaccinium myrtillus L.) is a perennial wild shrub, belonging to Vaccinium spp., and is a good source of natural phenolic compounds, such as anthocyanins, which provide the natural pigmentation of fruits and exhibit cardio and neuroprotective effects, and anti-inflammatory and anticarcinogenic properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of polyphenolic compounds are limited by their low absorption from the digestive tract [65,66]. It has been shown that chemical structure determined the rate and extent of their intestinal absorption.…”
Section: Health-promoting Properties and Application In Medicinementioning
confidence: 99%
“…The main classes of phenolic compounds present in the leaves and stems of Vaccinium myrtillus L. and Vaccinium vitis-idaea L. are phenolic acids (mainly chlorogenic acid), flavonoids, flavonol glycosides, and (epi)catechin monomers and oligomers [6,10,12,14,15,17,18], all known to be powerful antioxidants that act by directly trapping ROS, chelating transition metal ions, and inhibiting enzymes involved in the oxidative stress [19,20]. The recent studies conducted by Bujor et al [10,15] showed that phenolic compounds were found in significantly higher contents in the leaves and stems than in the fruits.…”
Section: Phenolic Composition Of Aerial Parts Of Vaccinium Myrtillus mentioning
confidence: 99%